ANALISIS KEBUTUHAN PENGEMBANGAN VIDEO INTERAKTIF BERPADUKAN METODE BLENDED LEARNING MATERI MENULIS CERPEN SEKOLAH DASAR - Rusfi Rama Dini; Sri Sumarni; Santi Oktarina (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research was conducted with the aim of analyzing students' needs for interactive video learning media combined with blended learning methods for short story writing material. In this research, the subjects chosen were 30 students from class V of the 148 Palembang state elementary schools. The data analysis techniques used are interview observations and questionnaires consisting of a student needs analysis questionnaire which covers aspects of learning needs, learning media needs and material understanding needs. Based on the results of the questionnaire, 66.7% of students strongly agreed that video media was used in learning to write short stories rather than theme books. further based on the results of the questionnaire regarding whether the teacher has carried out short story writing lessons blended learning Of the students' opinion, 60% disagree and 6.7% strongly agree. So from the results of the research that has been carried out it can be concluded pStudents really need interactive video learning media so that they can support a flexible learning process that can be studied anywhere, especially in short story writing material with the aim of making it easier for students to understand the material being taught in accordance with the objectives to be achieved so as to improve learning outcomes.